Physical exercise and COVID-19: a summary of the recommendations - Baisi Chagas, Eduardo Federighi; Biteli, Piero; Candeloro, Bruno Moreira; Rodrigues, Miguel Angelo; Rodrigues, Pedro Henrique [UNESP] (Amer Inst Mathematical Sciences-aims, 2020)
The rapid increase in the number of cases of corona virus (COVID-19) in 2020 and the lack of effective drug treatment, required the need for social restrictions measures, causing an important impact on the population's physical activity pattern. The decrease in the level of the population's physical activity is not only restricted to the practice of systematic physical exercise, but also the reduction of caloric expenditure with locomotor physical activities, work and leisure. Sedentary lifestyle is associated with an increased risk of the respiratory system infections and with more severe complications as well. On the other hand, systematic physical exercise has a positive effect on the immune system and in reducing the risk of diseases. However, high loads of physical exercise, with an increased amount or intensity, can compromise the immune system's response and increase the risk of respiratory infections. Thus, the aim of the study was to summarize the recommendations for physical exercise during the COVID-19 pandemic, and its relationship between exercise overload and health benefits.
Keywords: sedentary behavior; exercise; respiratory syndrome; coronavirus; COVID-19; pandemic